THE STUDY OF THE EXPENSES STRUCTURE ON THE MAINTENANCE OF RAILWAYS INFRASTRUCTURE - Mishchenko, M. I. (Science and Transport Progress, 2009)
The structure of railway transport expenses is investigated over studied the infrastructure objects as a factor influencing upon their values.